2021
DOI: 10.3389/fnagi.2021.664558
|View full text |Cite
|
Sign up to set email alerts
|

Gait Kinematic and Kinetic Characteristics of Older Adults With Mild Cognitive Impairment and Subjective Cognitive Decline: A Cross-Sectional Study

Abstract: BackgroundOlder adults with mild cognitive impairment (MCI) have slower gait speed and poor gait performance under dual-task conditions. However, gait kinematic and kinetic characteristics in older adults with MCI or subjective cognitive decline (SCD) remain unknown. This study was designed to explore the difference in gait kinematics and kinetics during level walking among older people with MCI, SCD, and normal cognition (NC).MethodsThis cross-sectional study recruited 181 participants from July to December 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…A significant increase in dorsiflexion and a decrease in plantar flexion under cognitive dual-task conditions were observed in patients with AD relative to the normal controls ( Rucco et al, 2017 ). More recently, Zhong et al (2021) found that older adults with MCI had larger knee peak extension angles and smaller knee heel strike angles than those with normal cognition. These previous studies suggest that cognitive impairment may affect gait kinematic parameters, along with spatio-temporal parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant increase in dorsiflexion and a decrease in plantar flexion under cognitive dual-task conditions were observed in patients with AD relative to the normal controls ( Rucco et al, 2017 ). More recently, Zhong et al (2021) found that older adults with MCI had larger knee peak extension angles and smaller knee heel strike angles than those with normal cognition. These previous studies suggest that cognitive impairment may affect gait kinematic parameters, along with spatio-temporal parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have stressed the importance of spatio-temporal gait features (i.e., slow gait velocity and shorter stride length and time) that can distinguish cognitive impairment ( Toots et al, 2019 ; Xie et al, 2019 ; Sebastiani et al, 2020 ). There has been little interest in gait kinematics according to cognitive status; two recent studies have provided evidence of an association between gait kinematics and cognitive status ( Rucco et al, 2017 ; Zhong et al, 2021 ). Rucco et al (2017) examined gait patterns in patients with AD and those with behavioral variants of frontotemporal dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were assigned to the MCI group if any one of the three following criteria were met ( Bondi et al, 2014 ; Zhong et al, 2021 ): (1) had an impaired score (> 1 SD below the age-corrected normative mean) on both assessments in at least one cognitive domain (memory, language, or executive function); (2) had one impaired score (> 1 SD below the age-corrected normative mean), in each of the three cognitive domains (memory, language, or executive function); or (3) Functional Assessment Questionnaire (FAD) scores ≥ 9. The standard deviation (SD)-based cut-offs utilized in our investigation were based on published studies in the Chinese population that had been adjusted for education and age ( Li et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Over time, multiple studies have examined the influence of different types of data on MCI: hear-disease-related data [ 41 ], demographic information [ 42 ], daily activities [ 43 ], or kinetic data [ 44 ].…”
Section: Implementation Of Ro-smartageing Systemmentioning
confidence: 99%